ONLINE TEACHING METHOD OF BASIC ENGLISH STRUCTURE VIA MOODLE SYSTEM - IRFAN HAMONANGAN TARIHORAN; ARDI PUTRA HIDAYAT (GANEC SWARA, 2023)
This research focuses on teaching methods used by three teachers of Basic English Structure. This study aims to answering the following research questions: (i) What are the methods of teachers in teaching Basic English Structure using Moodle system; (ii) How do the methods facilitate the teachers to teaching Basic English Structure using the Moodle. This study adopts qualitative research with descriptive approach. Three teachers and three students are interviewed whereas their working on online teaching is observed and then other supporting data are documented. The results of this study identifies that (1) teachers deliver material by three methods intensively (The most frequently-used method is Video Based Learning in speech delivery and Assignment Method for learning evaluation); (2) The role of the teaching methods involves ease of accessing material, long-term storage, time efficiency, and ease of presence list.